Agricultural Cooperatives from Uzbekistan and Their Activities (1917-1929 Years) - Alisherbek Usmanov (Genius Publishing Group, 2022)
This article describes the new economic policy imposed by the Bolsheviks in Uzbekistan in 1917-1929 after the Great October Socialist Revolution in Russia in 1917, its role and consequences in the social, economic, political, and cultural spheres of our country
Keywords: New; policy; communism; reform